Peningkatan Prestasi Akademik dan Non Akademik Peserta Didik: Implementasi Strategi Kepala Madrasah MAN 1 Bandar Lampung - Ridho, Muhammad; Kholid, Idham; Fauzan, A; Junaidah (STIES ALIFA, 2022)
Strategic management is the act of managing the potential of the organization toward excellence. The steps of strategic management include strategy formulation, implementation, and evaluation. Madrasah Aliyah Negeri 1 Bandar Lampung has shown the achievements of students both academically and non-academically. Of course, this achievement is inseparable from the visionary and democratic leadership of the madrasah head. This research adopts a qualitative approach by using data collection methods through observation, interviews, and documentation. The primary data sources used in this study are the head of the madrasah, the head of student affairs, students, and educators. Data analysis was carried out through three stages, namely data reduction, data display, and conclusion drawing. To ensure the validity of the data obtained, this study also used triangulation techniques as a validity test. The findings of this study include three aspects related to strategy formulation, strategy implementation, and evaluation in improving student achievement at MAN 1 Bandar Lampung.